2015
DOI: 10.1016/j.coph.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 inhibitors

Abstract: Tumors may adopt normal physiologic checkpoints for immunomodulation leading to an imbalance between tumor growth and host surveillance. Antibodies targeting the PD-1/PD-L1 checkpoint have shown dynamic and durable tumor regressions, suggesting a rebalancing of the host-tumor interaction. Nivolumab and pembrolizumab are the anti-PD-1 antibodies that are currently the furthest in clinical development, and anti-PD-L1 agents under investigation include MPDL3280A, MEDI4736, and BMS-936559. These agents have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
366
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(387 citation statements)
references
References 52 publications
2
366
0
7
Order By: Relevance
“…As an additional difficulty, the expression of PD-L1 may vary within the tumor and can be induced by previous therapies (21). That being said, patients with low tumor expression of PD-L1 do not respond as well as those with high expression, not only in melanoma, but also across different tumor types (22). In an analysis of melanoma patients treated with pembrolizumab, response rate varied between 57% when melanoma had a high PD-L1 expression, and 8% when there was not PD-L1 expression (23).…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…As an additional difficulty, the expression of PD-L1 may vary within the tumor and can be induced by previous therapies (21). That being said, patients with low tumor expression of PD-L1 do not respond as well as those with high expression, not only in melanoma, but also across different tumor types (22). In an analysis of melanoma patients treated with pembrolizumab, response rate varied between 57% when melanoma had a high PD-L1 expression, and 8% when there was not PD-L1 expression (23).…”
Section: Pd-l1 Expressionmentioning
confidence: 99%
“…Indeed, patients whose tumors are PD-L1(+) may not respond, while ~15% of patients with PD-L1(−) tumors demonstrate an antitumor response to therapy. 1 While tumor cell PD-L1 expression varied among melanoma subtypes, we found that when present, it was geographically associated with CD8+ T-cells, similar to most conventional cutaneous melanomas. Previous studies have supported the presence of a possible IFN-γ-mediated adaptive mechanism of PD-L1 display in uveal melanoma cell lines.…”
Section: Discussionmentioning
confidence: 57%
“…[1][2][3][4] Studies from our group and others indicate that the major mechanism driving melanoma tumor cell PD-L1 expression is an association with tumor-infiltrating lymphocytes (TIL), consistent with an endogenous antitumor immune response that may be unleashed with anti-PD-1/PD-L1 therapies. 5 Such adaptive PD-L1 expression by melanoma is not dependent on BRAF, NRAS, or c-KIT mutational status.…”
mentioning
confidence: 99%
“…PD-L2 has been demonstrated in B-cell lymphomas, and Hodgkin's disease (12) . PD-L1 is expressed in multiple normal tissues, and malignant cells while PD-L2 is essentially expressed from antigenpresenting cells (13)(14)(15) . Different from traditional cytotoxic chemotherapies or target treatments, evaluation of the effectiveness of immunotherapy poses some difficulties due to different reasons.…”
Section: Identification and Role Of Pd-1 And Its Ligands In Cancer Evmentioning
confidence: 99%